2022
DOI: 10.15252/embr.202254605
|View full text |Cite
|
Sign up to set email alerts
|

RAB6 and dynein drive post‐Golgi apical transport to prevent neuronal progenitor delamination

Abstract: Radial glial (RG) cells are the neural stem cells of the developing neocortex. Apical RG (aRG) cells can delaminate to generate basal RG (bRG) cells, a cell type associated with human brain expansion. Here, we report that aRG delamination is regulated by the post‐Golgi secretory pathway. Using in situ subcellular live imaging, we show that post‐Golgi transport of RAB6+ vesicles occurs toward the minus ends of microtubules and depends on dynein. We demonstrate that the apical determinant Crumbs3 (CRB3) is also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 74 publications
(99 reference statements)
0
12
0
Order By: Relevance
“…Consistent with the phenotypes of our Spast KO/KO mice, SEPT2 and NUDC also have established functions in regulating mitotic spindle architecture and in cytokinesis. Also consistent with the phenotype observed in null germ cells, the dynein–dynactin complex facilitates vesicle transport in multiple somatic cell types (reviewed by Liu, 2017 ; Reck-Peterson et al, 2018 ), including post-Golgi transport in mouse radial glial cells ( Brault et al, 2022 ), and SEPT2 has been shown to have roles in vesicle transport in Madin–Darby canine kidney (MDCK) cells ( Spiliotis et al, 2008 ). Of direct relevance to the mechanism of action of spastin in severing polyglutamylated tubulin and the aberrant transport of Golgi-derived vesicles during acrosome formation herein, published data suggest that SEPT2-based filaments facilitate post-Golgi vesicle transport along polyglutamylated microtubules ( Spiliotis et al, 2008 ), raising the possibility that SEPT2 has similar roles in male germ cells.…”
Section: Resultsmentioning
confidence: 61%
“…Consistent with the phenotypes of our Spast KO/KO mice, SEPT2 and NUDC also have established functions in regulating mitotic spindle architecture and in cytokinesis. Also consistent with the phenotype observed in null germ cells, the dynein–dynactin complex facilitates vesicle transport in multiple somatic cell types (reviewed by Liu, 2017 ; Reck-Peterson et al, 2018 ), including post-Golgi transport in mouse radial glial cells ( Brault et al, 2022 ), and SEPT2 has been shown to have roles in vesicle transport in Madin–Darby canine kidney (MDCK) cells ( Spiliotis et al, 2008 ). Of direct relevance to the mechanism of action of spastin in severing polyglutamylated tubulin and the aberrant transport of Golgi-derived vesicles during acrosome formation herein, published data suggest that SEPT2-based filaments facilitate post-Golgi vesicle transport along polyglutamylated microtubules ( Spiliotis et al, 2008 ), raising the possibility that SEPT2 has similar roles in male germ cells.…”
Section: Resultsmentioning
confidence: 61%
“…The results indeed indicated that Rab4A-Q72L mutant expression greatly increases KDELR1 expression at the PM, whereas S27N mutant failed to do so ( Figure 5 A), as shown by the surface biotinylation experiments. It is well known that Rab6A and Rab8A are small GTPases involved in the transport of post-Golgi vesicles [ 37 , 38 , 39 , 40 ]. We also tested whether the surface level of KDELR1-mCherry was changed after overexpressing Rab6A-Q72L/T27N and Rab8A-Q67L/T22N mutant pairs.…”
Section: Resultsmentioning
confidence: 99%
“…The growth inhibitory effect of statins in PPARGC1A silenced cells can be rescued by mevalonate or GGPP supplementation, or combinatorial expression of wild-type alleles of RAB6B and RAB27A. RAB proteins are key regulators of endosomal trafficking and linked to localization of proteins to plasma membrane 32 35 . RAB proteins require prenylation of the C-terminal CAAX using GGPP – a covalently attached lipid-moiety that allows membrane insertion 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%